Methodology for Determining Minimum Support Price for Minor Forest Produce in India - Sharma, Jitendra Vir; Gokhale, Yogesh; Jain, Nishant; Lele, Yatish A.; Tyagi, Aparna; Bhattacharjya, Souvik (Indian Forester, 2018)
Minor Forest Produce obtained from forests are a crucial commercial resource in the lives oftribals and other forest dwelling communities. More than 100 million rural people depend on the sale of minor forest produce for their livelihoods. These communities are legally empowered with governance of forests as well as ownership of the resource. Yet, not only do the communities remain impoverished, but also the unsustainable harvest of the resource from forests is a major cause of ecological stress. A research was conducted for developing methodology and determining the minimum support price for minor forest produce based on their labor input, insurance costs, traditional knowledge, resource availability, among other parameters, and assessed the status of the selected MFP resources in the country. The potential abundance, potential yield and sustainable yield of 12 selected MFPs across the studied states of India, have also been estimated.